In Vitro Evaluation of Lithium Disilicate Endocrowns and Post and Core Crowns—A Systematic Review - Qamar, Zeeshan; Alghamdi, Ahmed Mohammed Saad; Haydarah, Naji Khaled Bin; Balateef, Abdulateef Ahmed; Alamoudi, Ahmed Aydhah; Abumismar, Munther Amer; Mathur, Ankita; Minervini, Giuseppe (Journal of functional biomaterials, 2023)
The aim of this systematic review was to summarize the results of the studies that have compared the physical and mechanical properties of lithium disilicate (LDS) endocrowns constructed for posterior teeth to those retained by post-and-core retention systems. The review was conducted following the PRISMA guidelines. The electronic search process was conducted on PubMed-Medline, Scopus, Embase and ISI Web of Knowledge (WoS) from the earliest available date till 31 January 2023. Additionally, the studies were assessed for their overall quality and risk of bias using the Quality Assessment Tool For In Vitro Studies (the QUIN). The initial search resulted in 291 articles, out of which, only 10 studies met the eligibility criteria. In all studies LDS endocrowns were compared with various kinds of endodontic posts and crowns made from other materials. There were no definite pattern or trends observed in the fracture strengths of tested specimens. There was no predilection observed in failure patters among the experimental specimens. No predilection was observed in the fracture strengths of LDS endocrowns when compared to post-and-core crowns. Furthermore, no differences in failure patterns could be observed when both types of restorations were compared. The authors propose standardized testing of endocrowns against post-and-core crowns in future studies. In conclusion, long-term clinical trials are advocated to compare the survival, failure and complication rates of LDS endocrowns and post-and-core restorations.